UTILIZATION OF REBON PROTEIN HYDROLYSATE (Acetes erythraeus) AS PRESERVATIVE ON FRESH SALINE TILAPIA(Oreochromis niloticus) - Kenti Feoni Alda Sari; Suparmi Suparmi; Desmelati Desmelati (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2021)
ABSTRACT Protein hydrolysate of rebon shrimp (Acetes erythraeus) is a product produced from the breakdown of protein into simple peptides and amino acids through hydrolysis by enzymes, acids or bases. This product contains antioxidants and antibacterial compounds that can be used as preservatives. Saline tilapia (Oreochromis niloticus) is a very popular consumption fish, but this fish is easy to spoil, so it needs effective handling to maintain its quality. This study aims to determine the interaction between immersion time and the best concentration of rebon shrimp protein hydrolysate to maintain the shelf life of fresh saline tilapia. The research method consisted of two stages, namely: 1) Making rebon shrimp protein hydrolyzate 2) Soaking fresh saline tilapia with treatments, namely K1P1 (15% concentration+ 0 minutes), K2P2 (20% concentration + 30 minutes), and K3P3 (25% concentration + 60 minutes), 3 replicates with 27 experimental units. The results of the study of the best organoleptic values were the K3P3 treatment (concentration 25% + 60 minutes). Eye appearance value 9.00 (convex eyeball, clear cornea and pupil), gill value 8.97 (dark red and a little mucus), mucus value 8.73 (clear mucus layer), odor value 8.22 (fresh smell), meat incision value 8.93 (brilliant cut), texture 8.60 (solid and elastic). The pH value is 6.43, the lactic acid value is 11.1, and the TPC value is 1.3x105cfu/g. The best treatment can inhibit the growth of bacteria and maintain the quality of saline tilapia. Keywords: Protein hydrolysate, rebon shrimp, saline tilapia, Organoleptic